2012
DOI: 10.1111/jace.12019
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Structure and Electrical Properties of (KxNa0.96−xLi0.04)(Nb0.96−yTaySb0.04)O3 Piezoelectric Ceramics Modified with Manganese

Abstract: The effect of high doping levels of manganese (Mn) on the structure and electrical properties of (KxNa1−x)NbO3 (KNN) ceramics containing Li, Ta, and Sb has been investigated. The samples were measured using synchrotron X‐ray diffraction whereas Rietveld refinement with Fullprof was used to determine the structural information as a function of temperature. Temperature‐dependent dielectric measurement was used to compare the phase transition temperatures. The results show that Mn decreases the temperature range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…These curves, obtained from different temperatures, overlap into a single curve suggesting a perfect relaxation process and the other factors can be ignored. The relationship between the activation energy (E a ) related with the relaxation process, Boltzmann constant (k), absolute temperature (T), and pre-exponential factor (f 0 ), is given as 39 According to eqn (7), the activation energy (E a ) can be estimated from a straight line plot of ln(f max ) vs. 1000/T. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These curves, obtained from different temperatures, overlap into a single curve suggesting a perfect relaxation process and the other factors can be ignored. The relationship between the activation energy (E a ) related with the relaxation process, Boltzmann constant (k), absolute temperature (T), and pre-exponential factor (f 0 ), is given as 39 According to eqn (7), the activation energy (E a ) can be estimated from a straight line plot of ln(f max ) vs. 1000/T. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] They are highly likely to be the key material for light, computer and electronic information technologies and national defense military applications in the future. [4][5][6][7] In addition, most transparent piezoelectric ceramics could be used for energy storage. 8 Aer the discovery of transparency in 0.8(K 0.5 Na 0.5 )NbO 3 -À0.2SrTiO 3 ceramics was reported by Malic et al in 2004, 9 K 0.5 Na 0.5 NbO 3 lead-free transparent piezoelectric materials have attracted the attention of many researchers (the development is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Several research results on these KNN-based ceramics have been reported. The increase in piezoelectric properties was attributed in part to the coexistence of the orthorhombic and tetragonal phases and has also been investigated with synchrotron X-ray diffraction (Mgbemere, Fernandes et al, 2011;, 2013. According to Akdog an et al (2008) this phase coexistence is expected on the basis of Gibb's phase rule under isothermal and isobaric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Nb was considered a non-volatile ion, so we calculated (Na + K)/Nb ratio. The atomic number ratio of Na/Nb and K/Nb in the as-sintered state was almost the same to the nominal composition, 23) while Na/ Nb and K/Nb slightly decreased by 0.12 and 0.08 in the annealed sample for 8 h. As a result, the atomic number of (Na + K)/Nb in the annealed sample for 8 h was lower than 0.02 from the nominal composition. However, the annealed sample for 2 h showed the opposite behavior.…”
Section: Experimental Methodsmentioning
confidence: 76%